Load flow analysis using Newton-Raphson method in presence of distributed generation - Tebbakh Noureddine; Labed Djamel (International Journal of Power Electronics and Drive Systems (IJPEDS), 2021)
Distributed generations (DG), specially including renewable sources such as wind and sun are offering several opportunities for the currently in existence distribution networks and becoming one of the keys of treatment of its problems. Knowing the effects of each kind of DG on distribution networks is a primordial task because DG impacts differ from one kind to another. In this paper, we have analyzed and compared the effects of two kinds of DG, DG which provides real power only and DG which provides real power and reactive power at the same time connected at the critical bus in DN on the voltage profile, real and reactive power losses. We have proposed Newton Raphson method using Matlab to investigate the impacts of these two kinds of DG on 57-bus IEEE distribution test system. The obtained results have been exposed in detail at the end of this paper.